The generic context sharing protocol GCSP : Application to signaling in a cross-network and multi-provider environment - Chahine, Rony (2006)
This paper proposes a new signaling paradigm and a new signaling protocol called the Generic Context Sharing Protocol (GCSP) for the construction of a global control plane over present and future communication networks. After identifying the special nature of the control plane software involved in the setup of a conversational service instance it examines the various mechanisms for information sharing which leads to our new proposal. We show that this new data-based protocol is better suited to control plane requirements than the present day’s command-oriented signaling mechanisms. We indicate the basic principles of the protocol and we give a brief description of the generic context. We show the place of this proposal in the present day research efforts and we mention a practical implementation case.